Sorption of uranium(VI) ions by iron-containing nanocomposites based on montmorillonite - Zhdanyuk, N.V.; Kovalchuk, I.A.; Kornilovych, B.Yu. (Reports of the National Academy of Sciences of Ukraine, 2018)
We have studied physico-chemical features of the sorption of U (VI) ions by composites based on montmorillonite and organomontmorillonite modified by nanosized iron. The electron microscopic study of the obtained materials is performed. The possibility of their use in the purification of groundwater with the use of modern environmental technologies is shown.